Putting knowledge flows front and centre in health systems strengthening. Issue 2 (3rd July 2019) - Hanlin, Rebecca; Andersen, Margrethe Holm
ABSTRACT: This paper is a conceptual paper outlining a framework to analyse the main barriers linking knowledge production and application in the area of health in developing countries. It does so through a broad mapping and rethinking of the role of social and technological innovation in health systems strengthening. An analytical framework called the 4F framework – where the four Fs stand for Form, Field, Flows and Functions – is presented. By conducting a very high-level analysis of the barriers and enablers in knowledge production and application in the health sector in Kenya we give an indicative overview of the 4F Framework's potential. The empirical analysis suggests knowledge is often siloed into particular areas. At the macro level, there is insufficient focus on knowledge exchange between policy sectors i.e. health, industry, education. The analysis suggests that the framework provides a means to move from building 'health and wellbeing systems' to focusing on 'competence building systems in the area of health and wellbeing' which will provide a longer term holistic approach to health systems strengthening. The paper ends by presenting a number of recommendations for policy makers to ensure enhanced up-take of both technological and social innovation in health systems.